2008
DOI: 10.1093/ndt/gfn660
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic factors and patient perceptions are associated with attitudes to kidney transplantation among haemodialysis patients

Abstract: Negative attitudes to renal transplantation are associated with potentially modifiable factors. Based on this we suggest that it would be necessary to develop standardized, comprehensible patient information systems and personalized decision support to facilitate modality selection and to enable patients to make fully informed treatment decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
33
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 25 publications
8
33
0
5
Order By: Relevance
“…Ozminkowski et al found that African-American and white patients differed significantly in their expectations about the medical consequences and health outcomes of transplantation, in their religious objections to transplantation and personal attitudes about having a dead persons' organ in their body [43]. Similarly, expecting improved health after a transplant and foreseeing a decline in health on dialysis in our study were associated with positive attitude and willingness to have a transplant [42].…”
Section: Patient Preferences and Decision-making Towards Renal Transpsupporting
confidence: 49%
See 1 more Smart Citation
“…Ozminkowski et al found that African-American and white patients differed significantly in their expectations about the medical consequences and health outcomes of transplantation, in their religious objections to transplantation and personal attitudes about having a dead persons' organ in their body [43]. Similarly, expecting improved health after a transplant and foreseeing a decline in health on dialysis in our study were associated with positive attitude and willingness to have a transplant [42].…”
Section: Patient Preferences and Decision-making Towards Renal Transpsupporting
confidence: 49%
“…In our recent paper we reported that more than one-third of hemodialysis patients had false knowledge and beliefs about renal transplantation, and those patients were less likely to consider transplantation as a treatment option [42]. Ozminkowski et al found that African-American and white patients differed significantly in their expectations about the medical consequences and health outcomes of transplantation, in their religious objections to transplantation and personal attitudes about having a dead persons' organ in their body [43].…”
Section: Patient Preferences and Decision-making Towards Renal Transpmentioning
confidence: 95%
“…Some of these patients (78.31%) have expressed their willingness to be transplanted. Based on studies, this rate varies from 34.9% to 76% [8]- [15] and is similar to that reported in other African countries such as Morocco [15]. The reasons mentioned were essentially the willing to stop dialysis and to improve the quality of life.…”
Section: Discussionsupporting
confidence: 77%
“…The reasons mentioned were essentially the willing to stop dialysis and to improve the quality of life. The improvement of life quality has also been mentioned by patients in several studies [8] [9] [10] [15]. The lack of facilities for adequate haemodialysis in developing countries in general is a source of high rate of mortality and poor quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation